Diagnosis of cylindrical projections and analysis of suitability for the territorial area of South America - Barbosa, Leonardo Carlos (2021)
Cartographic Projection can be defined as the mathematical relationship between the position of a model of the terrestrial surface and the flat surface. Cylindrical projections are employed around the world, taking into consideration their properties and special characteristics. The purpose of this study was to identify the cartographic projection that best represents South America terrestrial surface, focusing mainly on the area of the continent, determined by the South American Defense Council. Initially, the projections were selected based on a bibliographic review. Subsequently, a suitability judgment was made for South America applying Tissot Indicatrix, Isolines of Maximum Angular Distortion and Region of Acceptable Distortion. Finally, an assumption was drawn up among the best results. The study control was performed using the software Flex Projector and ArcGIS 10.1, computational resources of great use in Cartography. The study provided a clear, simple and objective understanding of how different projections behave. The motivation comes from the insufficiency of detailed information and applied to the choice of map projection in regions of large areas.